CHEMOSIGNALS IN OLFACTORY SYSTEM MIGHT ALTER EMOTIONAL STATE: STRATEGY FOR SOCIAL COMMUNICATIONS - Akhtari, Zeinab; Salehi, Maryam; Saghian, Mohammad; Sahraei, Hedayat; Norouzi, Saba (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Olfactory system plays a crucial role in social and sexual behavior. Odors as olfactory stimuli can change immediate emotional state and level of arousal in humans. It is demonstrated that brain in the perception, discrimination and recognition of odor memory employs the amygdala and hypothalamus by different sets of cortical areas. Moreover, brain has the potential to instantly recall the emotional valance and personal experiences related to the source of the odor (smell) in human which may affect correct decision making. Moreover, chemosignals (pheromones) are an important and critical means of communication for most mammalian species. Most mammals respond to chemosignals in many ways, including those surrounding reproduction, parent-offspring interactions and territorial/dominance relationships. They affects the olfactory neurons of the nervous system, then stimulating the central nervous system consequently influencing the hormonal system leading to release of neurotransmitters by indirectly influencing the behavior. In mammalian behavior which affects the living maintenances and quality. This issue has been discussed in religious doctrine in order to protect the nervous system from damage caused by the nuisance odors